(untitled) (Global Journal of Science Frontier Research, 2020)
Human communication has developed over thousands of years with contributions to the development of written alphabets and numerals coming from the ancient Phoenicians, Sumerians, Egyptians, Chinese, Greeks, Romans, Indians and Arabs. Our objective in this paper is to introduce new forms of alphabets and numerals which have been developed by us as our personal contribution to the subject of human communication. We developed these characters about ten years ago and now we feel it is time to publish it in a short communication. In this paper, we review some of the literature pertaining to the development of writing and then we introduce the new forms of writing developed by usby stating forward how these new forms of writing can be applied in the real world of human communication. We hope that the new numerals and alphabets will be useful in the fields of encryption, cryptology, and education.